Artificial Neural Network Based Particle Swarm Optimization for Microgrid Optimal Energy Scheduling - Abdolrasol M.; Mohamed R.; Hannan M.; Al-Shetwi A.; Mansor M.; Blaabjerg F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electromagnetic wave emission; Meteorology; Microgrids; Particle swarm optimization (PSO); Scheduling; Solar energy; Solar power generation; Wind; Battery status; BPSO algorithms; Learning rates; Optimal energy; Optimal values; Solar irradiation; Sustainable resources; Virtual power plants (VPP); Neural networks